Development of an Interactive Educational Website “Anti Online Gambling” as an Effort to Improve Moral Reasoning Among The Public - Saves Anggiat Sitompul; Nuruddin Hady; Nur Wahyu Rochmadi (Journal of Educational Sciences, 2026)
This study aims to develop an interactive educational website called “Anti Judi Online” (Anti Online Gambling) as a medium to improve public moral reasoning regarding the negative impacts of online gambling. The research method used is the waterfall development model, which includes the stages of analysis, design, implementation, testing, and maintenance. Expert validation of the content and media indicates that the product is suitable for use as an educational tool, with content aligned with moral principles and legal regulations, and meeting usability and user experience (UX) standards. Testing on small and large groups demonstrated improvements in users' moral reasoning, legal awareness, and critical attitudes toward the dangers of online gambling. The website has proven effective in enhancing moral reasoning and changing users' attitudes. This study recommends the use of the product by the public as a digital educational medium, and encourages the government and educational institutions to integrate similar media into technology-based prevention programs. Further development through mobile platforms and expansion of social issues are important agendas for future research.